187 Between a Rock and a Hard Place: Challenges in Treating Patient with Phagophobia and Comorbid Panic Disorder and Severe Anorexia. (April 2020) - Yen, Po Yu; Akram, Faisal; Naqvi, Syed
Abstract: Phagophobia is a rare form of psychogenic dysphagia; it is characterized by an intense fear of swallowing food. It is a disorder which may be potentially life threatening if left untreated. Different effective approaches regarding the management for phagophobia have been documented in the past. However, there have not been sufficient data to support a definitive treatment. We would like to present a case which phagophobia, along with the presence of panic disorder and severe anorexia increase the difficulty in patient management. Patient is a middle-aged female with history of anorexia nervosa and panic disorder. She presented with an eight-month history of inadequate caloric intake which was related to her fear of gaining weight and being preoccupied with intense fear of intake of food and medications; she stated that her throat was burning in attempt to swallow solids. She also stated that she felt like she had a "lump" in the throat. Her intake of food was limited to only certain types of food. However, after eating, she would engage in purging behaviors. Her hospitalization was complicated by multiple panic attacks in a day. Patient underwent diagnostic interventions that helped us ruled out the other underlying causes of her symptoms: physical examinations, laboratory findings, bedside swallowing evaluation and esophagogastroduodenoscopy. These evaluations indicated that her symptoms were not caused by a medical condition or physiological effects of a substance. Daily medications aided with Anxiolytics as needed were prescribed for managing her symptoms. Non- pharmacological managements following the recommendations of the expert in positive behavior support were performed aiming to treat her symptoms. Due to intense fear of swallowing, she was not able to take oral medications for panic disorder, and the effect of psychotherapy for eating disorder was limited due to frequent recurrence of panic attacks. She had not shown improvement of her symptoms: inadequate daily energy intake and medication, non-compliance to oral medications. Her BMI dropped from 14 to 13 over the course of 8 months and the symptoms of panic disorder persisted, and she is at risk of medical emergencies. In this report, we present the challenges in managing a patient with multiple psychiatric comorbidities, where each illness increased the difficulty of treating another illness. We had reviewed case reports which indicated that cognitive behavioral techniques may be beneficial to patients with phagophobia. However, the effects of non-pharmacological managements were limited as patient's psychiatric illness prevented her from completing each session. To this date, there has been no report of treatment success in a patient whose situation is similar to hers. Further research, clinical trials, and additional data collected in the future may provide new insights into management of this therapeutic challenge.